ANALISIS KEBUTUHAN TENAGA KERJA DAN PERALATAN PADA PROYEK PENINGKATAN JALAN: Studi Pada Pelaksanaan Proyek Peningkatan Jalan Pancor - Rempung - INDRA ARISANDI; I GEDE PUTU WARKA; ZAEDAR GAZALBA (GANEC SWARA, 2018)
The Pancor-Rempung road improvement project is delayed. Implementation planning, so that it is needed to optimize the use of labor and equipment so that time and costs can be controlled properly.The analysis is carried out by calculating the production capacity of each heavy equipment, in order to obtain the value of productivity and labor coefficient. Productivity values and labor coefficients are used to calculate labor and peratan needs based on implementation time schedules and based on optimization of equipment production capacity.From the results of the calculation of labor requirements and equipment based on time schedule, the need for 1 unit excavator (196 hours), 7 units of dump trucks (588 hours), 3 units of motor grader (343 hours), 2 unit wheel loaders (588 hours), vibrator roller 3 units (343 hours), water tank truck 2 units (441 hours), aspalt mixing palnt 1 unit (245 hours), asphalt finisher 1 unit (245 hours), tandem roller 1 unit (245 hours), pneumatic tire roller 1 unit (245 hours), 1 unit air compressor (245 hours), 1 unit asphalt sprayer (245 hours), 1 unit concrete pan mixer (98 hours, concrete truck mixer 3 units (98 hours), 4 workers (686 hours ), and foreman 4 people (686 hours), with a total cost of IDR 4,074,053,795.00 while the need for labor and equipment based on optimization of equipment production capacity, obtained the need for 1 unit excavator (28 hours, 24 truck dump trucks (105 hours ), motor grader 1 unit (98 hours), wheel loader 1 unit (105 hours), roller vibrator 1 unit (98 hours), water tank truck 1 unit (98 hours ), aspalt mixing palnt 1 unit (35 hours), asphalt finisher 1 unit (35 hours), tandem roller 1 unit (35 hours), pneumatic tire roller 1 unit (35 hours), air compressor 1 unit (35 hours), asphalt sprayer 1 unit (35 hours), concrete pan mixer 1 unit, (28 hours), concrete truck mixer 9 units (28 hours), workers 9 people (161 hours) and foreman 2 people (161 hours), with a total cost of Rp. 1,382,258,857.00. In calculating labor requirements and equipment based on the time schedule obtained several jobs have a small time factor of labor and equipment, due to the long duration of work time and good equipment production capacity.